Increasing Middle-Class and Its Socio-economic Impacts on South Asia - Gokarna Prasad Gyanwali (Journal of Islamic Economics Perspectives, 2025)
Middle Class is a more perplexing and debatable phrase in social science. Lower, medium, and upper or high middle classes are recognized as the three categories inside the middle class. The new powerful middle-class appearance in developing countries has been generating difficulties in defining and making sense of the concept. The new or emergence of the middle class is a big issue, opportunity, and challenge in South Asia and the world. According to Lu, Marcus (2023)[1], 113 million people will become middle-class worldwide in 2024 and the majority of them are coming from Asia. More than 100 million people worldwide join the middle class each year. The report of the Asian Development Bank (2011)[2] indicates that a billion people were in the middle class in 2011, it will be 1.2 billion by 2030, and 1.4 billion by 2050. This paper tries to articulate the situation of the middle class and its impacts on the socio-economic life in this region. This article uses the ADB (2011) definition of middle-class consuming those with consumption spending between $2 to $20 per day at 2005 PPP$.